POTENTIAL FOR DIABETIC WOUND HEALING WITH HYDROGEL PATCH OF NEEM LEAF EXTRACT (AZADIRACHTA INDICA) - LESTARI, NITA W.; WIJIANTO, DISKI W.; WAHYUNI, ARIFAH S. (International Journal of Applied Pharmaceutics, 2025)
Objective: Disruptions in the wound healing process occur because of two main factors in diabetes: high blood sugar levels and chronic inflammation. This study evaluated the effectiveness of hydrogel patches containing neem leaf extract in the healing of diabetic wounds. Methods: The experimental method used a post-test control group design that included extract preparation, phytochemical screening, hydrogel patch preparation, stability testing, and testing of hyperglycemic rats by observing wound size, histopathology, and TNF-α and TGF-β cytokine levels on days 7, 14, and 21. Results: The neem leaf extract contains secondary metabolites that support anti-inflammatory and wound-healing activities. Stability tests showed that the hydrogel patch met the standards for organoleptic properties, weight uniformity, and moisture absorption. The group given NLEHP (Neem Leaf Extract Hydrogel Patch) showed a decrease in wound area (0.5±0.1 cm2) not significantly different from the non-diabetic group with a reduction (0.5±0.1 cm2) (p>0.05) and significantly different from the negative group with a decrease (1.1±0 cm2) (p<0.05). Histopathological analysis of skin thickness of the NLEHP group (19.2±1.6 μm) was not significantly different from the non-diabetic group (18.2±0.8 μm) (p>0.05) and significantly higher than the negative control group (10.7±2.4 μm) (p<0.05). The TNF-α levels showed a significant increase (p<0.05) in the negative control group, whereas the non-diabetic and NLEHP groups showed a non-significant decrease (p>0.05). The levels of TGF-β progressively increased in the non-diabetic and NLEHP groups, unlike the decline observed in the negative control. Conclusion: These results indicate that the neem leaf extract hydrogel patch is an effective alternative for diabetic wound healing therapy.